Incertidumbre en la educación remota: Aproximación fenomenológico-hermenéutica a la experiencia estudiantil según Van Manen, Lima. - Castillo Gil, Cecilia Isabel (2025)
The purpose of the research was to analyze the meanings of the experience of uncertainty in remote education in students of a public university, in Lima, 2022. A hermeneutical phenomenological approach based on Max van Manen's proposal was used and data were collected through anecdotes and conversational interviews. The analysis followed a process of thematic reflection aimed at identifying essential structures of the experience. The results arose from the analysis of the participants' discourses through thematic coding and hermeneutical interpretation.  As a conclusion, it was obtained that the meanings attributed to the experience of uncertainty were boredom, stress, dissatisfaction with the training received, and adaptation, which was disparate, depending on the career or place of origin. This last aspect allowed feelings to be expressed, such as secure attachment, which allows facing the uncertainty of the context.